Reconstructing Teacher Professionalism: Integrating Digital Literacy and Innovative Pedagogy in the Era of Technological Disruption - Ira Rikmasari; Linda Yuliandini; Susi Sugiarti; Sofyan Iskandar (Papanda Publisher, 2026)
The digital transformation of education necessitates fundamental reconstruction of teacher professionalism, requiring integration of digital literacy and innovative pedagogy as core competencies for 21st-century educators. This phenomenological qualitative study explored lived experiences of six primary school teachers from three schools in Bandung City, Indonesia, selected through purposive sampling. Data were collected through in-depth semi-structured interviews, participatory classroom observations, and document analysis over one month, then analyzed using Braun and Clarke's thematic analysis framework. Analysis revealed five interconnected themes: professional identity reconstruction in digital spaces, emotional and structural dynamics of technological adaptation, digital literacy as multidimensional metacognitive competence, innovative pedagogy as reflective transformation, and development of professional agency with continuous learning dispositions. Teachers experienced digital integration as transformative processes involving disorientation, critical reflection, and identity negotiation rather than linear skill acquisition. Significant disparities emerged between urban and semi-urban contexts, with collaborative learning communities accelerating transformation regardless of resource constraints. Findings extend Transformative Learning Theory and TPACK framework by proposing digital professional agency as an integrative construct encompassing technical-pedagogical competence, critical consciousness, reflective capacity, collaborative disposition, and contextual adaptability. Results emphasize that 21st-century teacher professionalism represents humanistic transformation positioning educators as reflective adaptive agents rather than mere technological adopters.